The Treatment of Ingrown Toenails: A Retrospective Study of Combined Wedge Resection with Phenol Versus Silver Nitrate Cauterization - Badriya Al-Lenjawi; Zaghloul Gouda; Julius Curameng; Diovani Mendoza; Abdu Razak Vattathu (Dermatology, 2018)
Aim The aim of the current study is to retrospectively review the efficacy of phenol versus silver nitrate matricectomy for treating ingrown toenails. Methods A total of 132 charts for ingrown toenails treated at Umm Ghuwailina Primary Health Care Center, Doha, Qatar were retrospectively reviewed for association with socio-demographic characteristics, infection rate, pain level, duration of treatment, treatment modalities and their outcomes. Results A total of 64 phenol ablations and 68 silver nitrate ablations were performed on patients with stages II and III diseases. The patients were reviewed daily until the achievement of full wound healing and later on, they were regularly followed-up for a mean period of 36 months. In the phenol group, the healing period post-operatively ranged from 2 to 4 weeks with no post-operative complications including loss of sensation or nail spikes with only one recurrence (0.57%) were observed, after 16 months. On the other hand, the silver nitrate group had a longer healing period ranging from 4 to 10 weeks with post-operative complications ranging from post-operative nail bed infection (soft tissue necrosis) (43%), post-operative pain (65%). The success rate was found to be 98.8%. Treatment with phenol therapy and 96% with silver nitrate therapy respectively. Conclusion We conclude that both phenol and silver nitrate cauterization are an excellent method for the treatment of ingrowing toenail. However, phenol is far superior to silver nitrate due to its simplicity, low morbidity, pain-free course post-operatively, no postoperative infection, better satisfaction and high success rate. Before surgical intervention, 79% of patients had a severe pain score, 72% had difficulty wearing their normal footwear and 65% had the restriction of normal activities due to their ingrown toenails. Overall, 100% of phenol arm were satisfied (n=63) with the procedure whereas in the silver nitrate arm only 82% (n=56) were satisfied. No loss of sensation at the surgical site was reported in either of the arms.